Revisit coal consumption, CO emissions and economic growth nexus in China and India using a newly developed bootstrap ARDL bound test - Feng-Li Lin; Roula Inglesi-Lotz; Tsangyao Chang (Energy Exploration & Exploitation, 2018)
This study revisits coal consumption, CO 2 emissions and economic growth nexus for both China and India using a newly developed Bootstrap ARDL model over the period of 1969–2015. Empirical results indicate no long-run relationship among these three variables for both China and India, and Granger causality test based on Bootstrap ARDL model indicates a feedback between coal consumption and economic growth, between economic growth and CO 2 emissions and between coal consumption and CO 2 emissions in China. However, we find a one-way Granger causality running from coal consumption to economic growth and the feedback hypothesis is confirmed between economic growth and CO 2 emissions and between coal consumption and CO 2 emissions in India. The coefficients signal that coal consumption is an important factor towards the promotion economic growth in both China and India. For China, higher economic growth reduces CO 2 emissions, while for India, it further increases CO 2 emissions. Our empirical results have important policy implications for the government conducting effective energy polices to promote economic growth in both China and India.